It's powwow time! - Troian, Martha (Greenwillow Books, an imprint of HarperCollins Publishers, 2024)
"Bineshii is looking forward to his first powwow. He wakes up and travels with his mother to the community event. He eats bannock and drinks strawberry juice as he watches the dancers perform. And ever so slowly, Bineshii works his way from the edge of the circle watching the dancers to inside the circle itself, dancing and celebrating with everyone else. Award-winning journalist Martha Troian’s child-centered text and Hawlii Pichette’s action-packed illustrations build excitement on the page as Bineshii’s curiosity and confidence grows. It’s Powwow Time! explores the rewards of being open to new experiences while also serving as a beautiful and informative introduction to a First Nations powwow. " --